Programas de assistência farmacêutica do governo federal: Estrutura atual, evoluç\~ao dos gastos com medicamentos e primeiras evidências de sua eficiência, 2005-2008 - Adriana Pacheco Aurea; Luís Carlos G. de Magalh\~aes; Leila Posenato Garcia; Carolina Fernandes dos Santos; Raquel Filgueiras de Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– Health care, including access to medicines, is granted as a citizen's right by the Brazilian Constitution through a national health system called Unified Health System (SUS). The Pharmaceutical Care Programmes of SUS are, quite often, the only way a large part of the population has to obtain medication. These programmes exert strong pressure on the public health resources. Due to the importance of the Pharmaceutical Care for the Brazilian population, the main objective of this study is to analyse the federal government purchase of medicines over the period 2004-2008. This study also includes a preliminary exercise in order to evaluate federal government bidding efficiency in the purchase of medicines, over the period 2005-2009, considering the pharmaceutical care programmes of Hereditary Coagulopathies and Diabetes. The main database used in the study, although extremely useful, has been rarely applied for such purpose. Expenditure values of medicines purchased through bidding were obtained from the records of a system of the federal government called Sistema de Administraç\~ao de Serviços Gerais (SIASG). The spending on procurement of medicines, at least those that are part of the pharmaceutical care programmes under the responsibility of the Ministry of Health and whose purchases are centralized, showed relative stability over the period 2005-2008. The study found evidences pointing to the possibility of purchase concentration of certain medicines over the time. There are indications - that should not be hastily generalised - that some pharmaceutical care programmes that are under the responsibility of the Ministry of Health have achieved efficiency gains that are not negligible. For example, while the quantities of NPH human insulin acquired over the period remained relatively constant, its total expenditure reduced due to the decrease in the price paid per unit purchased. It may help to explain the fact that, despite the relative stability of federal spending on the purchase of medicines, pharmaceutical care under the responsibility of the Ministry of Health seems to have expanded its coverage.
Keywords: I18; 330; Gesundheitsversorgung; Gesundheitswesen; Pharmazeutisches Produkt; Brasilien